Gambaran Riwayat Pemberian Air Susu Ibu dan Status Gizi Balita di Dusun Ratan Kecamatan Batur Kabupaten Banjarnegara - Fini Khafillah; Lina Handayani (Jurnal Cakrawala Promkes, 2022)
Background: The best food for newborns up to six months of age is breast milk. This is due to the complete nutritional content so that it can meet the baby’s needs. Breastfeeding after the baby is six months old is recommended with complementary feeding. The percentage of exclusive breastfeeding in Banjarnegara Regency in 2019 was 61.4%. History of breastfeeding factors that can influence the nutritional status of children. This study aims to describe the history of breastfeeding and the nutritional status of children in Dusun Ratan, Batur Village, Batur District, Banjarnegara Regency. Method: This study uses a qualitative method with a case study approach. There were nine informants in this study consisting of mothers who had toddlers with the criteria of under-fives being less nutritional status, over nutritional status, and good nutrition status. Collecting data in this study through interviews. Result: Most of the informants gave exclusive breastfeeding. But one of the informants who had a toddler with more nutritional status did not exclusively breastfeed. The knowledge of the informants is not good. This may be related to the level of education of the informants which is still low on average. A mother’s motivation in breastfeeding comes from herself and also her family. Information about breastfeeding was obtained by informants through counseling, KIA books, the internet, articles on breastfeeding, and midwives. Conclusion: The history of exclusive breastfeeding is related to the nutritional status of toddlers, although exclusive breastfeeding is not the only factor that can determine the nutritional status of toddlers. Husband and family